2005
DOI: 10.1262/jrd.17019
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced Changes in Sympathetic Innervation of Porcine Ovaries and in Their Steroidogenic Activity

Abstract: Abstract. The aim of the present study was to determine changes in the density of sympathetic nerves in porcine ovaries with dexamethasone (DXM)-induced cysts and the alterations in steroidogenic activity and amounts of catecholamines in the affected gonads. Cystic ovaries were supplied by numerous sympathetic nerve fibers. The amount of noradrenaline in the cysts (fluid, wall) was significantly higher than in the large follicles of the control group. After DXM injections, the amounts of noradrenaline and adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
3
8
1
1
Order By: Relevance
“…Glucocorticoids have been shown to enhance sympathetic innervation of other tissues (e.g., ovary) (Jana et al, 2005), and they can interact with ␤-adrenergic signaling to enhance the transcription of NGF (Colangelo et al, 2004). However, previous studies have shown that the social stress model used here leads to a reduction in circulating glucocorticoid levels ), which would not be able to explain the increased innervation observed in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…Glucocorticoids have been shown to enhance sympathetic innervation of other tissues (e.g., ovary) (Jana et al, 2005), and they can interact with ␤-adrenergic signaling to enhance the transcription of NGF (Colangelo et al, 2004). However, previous studies have shown that the social stress model used here leads to a reduction in circulating glucocorticoid levels ), which would not be able to explain the increased innervation observed in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…The weight, length and height of the pathologically changed ovaries were diminished, what may results from the presence of partially luteinized follicular cysts, the reduction in the number of small ovarian follicles (1-3 mm in diameter) and a total lack of both the medium-sized follicles and CL. Similar results were previously found in the pigs after adrenocorticotropic hormone (ACTH) or DXM treatment [9,11,20,21].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, our pilot study showed that dexamethasone (DXM) injections in gilts from day 16 of the first studied estrous cycle until day 9 of the second studied cycle, lead to changes in the of P450 scc , 3β-HSD and P450 arom protein expression, as well as in the content of progesterone (P 4 ), androgens and estrogens in ovarian structures [9]. It is generally known that the morphological and functional changes of polycystic ovaries are closely dependent on the phase of estrous cycle, in which the administration of cyst-induced hormones was started [10][11][12].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has recently been shown that not only is the density of sympathetic nerve fibers increased in the cystic ovaries of women [4], rats [5,6] and pigs [7], but also the cholinergic innervation undergoes a profound remodeling in porcine ovaries treated with dexamethasone phosphate disodium salt (DXM) [8]. Furthermore, it has been found that laparoscopic resection or cauterization of the medullar part of cystic ovaries -i.e.…”
Section: Introductionmentioning
confidence: 99%